Risk factors for the severity and mortality of pneumococcal pneumonia: Importance of premorbid patients' performance status. Issue 10 (October 2016) - Ishiguro, Takashi; Kagiyama, Naho; Uozumi, Ryuji; Odashima, Kyuto; Kurashima, Kazuyoshi; Morita, Satoshi; Takayanagi, Noboru
Abstract: Comorbidity is known to be associated with the severity and mortality of pneumonia. The severity of each underlying disease varies, and performance status, which is known to be a prognostic factor of malignant diseases, reflects the overall patient condition as affected by his/her comorbidity and underlying diseases of various severity. We investigated whether premorbid patients' performance status is associated with the severity and mortality of pneumococcal pneumonia. This retrospective study assessed these factors in hospitalized patients suffering from pneumococcal pneumonia from 2002 to 2015. We included 424 patients aged 68.9 ± 14.1 years in the study, of which 68.9% were men. A multivariate analysis found that advanced age (≥65 years), diabetes mellitus, and poor performance status were independent factors associated with severity, whereas old pulmonary tuberculosis, poor performance status, pneumococcal bacteremia, and severe pneumonia were independent factors that were associated with non-survival. Poor performance status was associated with the severity and mortality of pneumococcal pneumonia.